Root growth and yield of sugarcane as a function of increasing gypsum doses - Clemente, Paulo Ricardo Aprígio; Bezerra, Breno Kennedy Lima; Silva, Vinicius Santos Gomes Da; Santos, Jhulyanne Christiny Marcelino Dos; Endres, Laurício (Escola de Agronomia/UFG, 2017)
ABSTRACT Sugarcane plays an important role in the Brazilian agribusiness. However, poor rainfall distribution and soil acidity directly affect its production in the Northeast Brazil. Gypsum improves the soil physical and chemical properties, attenuating the effects of water stress and acidity in the edaphic environment. This study aimed at determining the effect of gypsum doses on sugarcane growth and yield. A field experiment was conducted using a 3 x 5 factorial arrangement organized in a randomized block design, with four replications. Treatments consisted of a combination of three sugarcane varieties (RB011941, RB92579 and RB991536) with five gypsum doses (0 Mg ha-1, 2.5 Mg ha-1, 5.0 Mg ha-1, 10.0 Mg ha-1 and 20.0 Mg ha-1). RB92579 exhibited the highest stalk (157.90 Mg ha-1) and sugar (24.10 Mg ha-1) yield. Gypsum did not influence the sugarcane yield or plant growth in the vegetative growth stage, but, in the maturation phase, the leaf area declined and the number of shoots increased with the rise in gypsum doses. Applying gypsum increased the roots density along the soil profile, with a rise of around 1.10 g dm-3 at the most technically efficient dose (12.5 Mg ha-1), however, yield was not influenced, maybe due to the effect of high rainfall during the entire crop cycle. Thus, higher gypsum doses are recommended during periods of drought to benefit from the resulting increased root system.

RESUMO A cana-de-açúcar possui grande expressão no agronegócio brasileiro, entretanto, a má distribuição hídrica e a acidez do solo afetam diretamente sua produção no Nordeste do Brasil. O gesso proporciona melhorias nas propriedades físicas e químicas do solo, atenuando os efeitos da falta de água e acidez no ambiente edáfico. Objetivou-se determinar o efeito de doses de gesso no crescimento e produtividade da cana-de-açúcar. O experimento foi conduzido a campo, utilizando-se delineamento em blocos ao acaso, no esquema fatorial 3 x 5, com quatro repetições. Os tratamentos consistiram da combinação de três variedades de cana-de-açúcar (RB011941, RB92579 e RB991536) com cinco doses de gesso (0 Mg ha-1; 2,5 Mg ha-1; 5,0 Mg ha-1; 10,0 Mg ha-1; e 20,0 Mg ha-1). A RB92579 apresentou maior produtividade de colmos (157,90 Mg ha-1) e de açúcar (24,10 Mg ha-1). O gesso não influenciou na produtividade da cana ou no crescimento das plantas, na fase de crescimento vegetativo. Já na fase de maturação, a área foliar diminuiu e o número de perfilhos aumentou, com o aumento das doses de gesso. A aplicação de gesso aumentou a quantidade de raízes ao longo do perfil do solo, com incremento da ordem de 1,10 g dm-³ na dose de maior eficiência técnica (12,5 Mg ha-1), porém, não influenciou na produtividade, talvez pelo efeito da alta pluviosidade durante todo o ciclo da cultura. Portanto, doses de gesso mais elevadas são recomendadas durante períodos de seca, beneficiando-se, assim, do aumento no sistema radicular proporcionado pela sua aplicação.
Crescimento radicular e produção de cana-de-açúcar em função de doses crescentes de gesso
Keywords: Saccharum spp.; gipsite; root system; Saccharum spp.; gipsita; sistema radicular